(untitled) (CIPEEX, 2023)
THIS PAPER PRESENTS THE ’STATE OF THE ART’ SCHEDULED FOR THE PREPARATION OF A MASTER’S THESIS MASTER’S DISSERTATION THAT IS BEING DEVELOPED IN THE STRICTO SENSU POSTGRADUATE PROGRAM IN ENVIRONMENTAL ENVIRONMENTAL SCIENCES AT THE EVANGELICAL UNIVERSITY OF GOIÁS (UNIEVANGÉLICA). THE IMPORTANCE OF THE IMPORTANCE OF STUDIES FOCUSED ON GOAL 12 OF THE NATIONAL COUNCIL OF JUSTICE, WHICH CALLS FOR ENVIRONMENTAL ACTIONS THAT CONVERGE TOWARDS ENVIRONMENTAL SUSTAINABILITY. IN ORDER TO SUCCEED, A DEDUCTIVE APPROACH WAS USED, ENHANCED BY BIBLIOGRAPHIC AND DOCUMENTARY TECHNIQUES, WHICH DEVELOPED IN A DESCRIPTIVE AND EXPLANATORY ALLOWED THE RESEARCH TO BE DESCRIPTIVE AND EXPLANATORY NATURE.